Pengaruh Desentralisasi Fiskal dan Pertumbuhan Ekonomi Terhadap Kemiskinan Provinsi Bali - Sudewi, Ni Nyoman Ayu; Wirathi, I G.A.P (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2013)
The passage of fiscal decentralization policies have a positive impact on the development of potentiality and creativity of local government. Effectiveness in managing the wealth of the area will affect the local income then afterwards make use for prosperity society. The purpose of this study was to determine the effect of fiscal decentralization and economic growth to the poverty. The method that use is multiple linear regression analysis techniques. The result simultaneously showed that fiscal decentralization and the economic growth have a significant effect. Partially, the result showed that fiscal decentralization have a negative effect and significant and the economic growth have a negative effect and significant on povertyof the low percent in total poor society.
Keywords: Fiscal Decentralization; Poverty; Economic Growth